2019
DOI: 10.1038/s41423-019-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of S100A10 in Toll-like receptor signaling and immunity to infection

Abstract: Toll-like receptors (TLRs) are key pattern recognition receptors that mediate innate immune responses to infection. However, uncontrolled TLR activation can lead to severe inflammatory disorders such as septic shock. The molecular mechanisms through which TLR responses are regulated are not fully understood. Here, we demonstrate an essential function of S100A10 in TLR signaling. S100A10 was constitutively expressed in macrophages, but was significantly downregulated upon TLR activation. S100A10-deficient macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Luciferase reporter gene assays were performed as described previously [41]. Briefly, HEK293 cells were transfected with an IFN-β/ISRE luciferase reporter plasmid and a Renilla luciferase plasmid as an internal control plus the indicated plasmids.…”
Section: Luciferase Reporter Gene Assaymentioning
confidence: 99%
“…Luciferase reporter gene assays were performed as described previously [41]. Briefly, HEK293 cells were transfected with an IFN-β/ISRE luciferase reporter plasmid and a Renilla luciferase plasmid as an internal control plus the indicated plasmids.…”
Section: Luciferase Reporter Gene Assaymentioning
confidence: 99%
“…Bone marrow-derived macrophages (BMDMs) were generated as described (17,29). The purity of BMDMs was more than 95% as determined by CD11b + and F4/80 + flow cytometry staining.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Anti-inflammatory related Cfl1, Gng12, Manf, and Ptpn6 proteins show high expression in the S3 state and then decrease again. Notably, S100a10, Rps28, Irg1, and Ptgs2 proteins increase the amount of abundance from S4 to S3, which is the most active period of macrophages, showing that cells at that time have a proinflammatory function 31, 40, 41 . Through trajectory analysis, we found that Arglu1, Nip7, Nudcd2, and Mtmr2 proteins, whose functions are not yet known for the activation of macrophages, elevate in S4 and then gradually decrease with time.…”
Section: Resultsmentioning
confidence: 99%